2016
DOI: 10.4236/jacen.2016.52008
|View full text |Cite
|
Sign up to set email alerts
|

Edible Ectomycorrhizal Mushrooms <i>Russula</i> spp. of Côte d’Ivoire: Total Phenolic Content, HPLC-Profiles of Phenolic Compounds and Organic Acids, Antioxidant Activities

Abstract: The aim of this study was to investigate the phenolic compounds content, HPLC-profiles of phenolic compounds and organic acids, and also antioxidant activities via the ability to scavenge DPPH radical of three wild edible mushrooms belonging to Russula genus and being collected in center of Côte d'Ivoire. Total phenolic compounds, flavonoids and tannins contents of methanolic extracts were assessed by colorimetric assays. So, the obtained values of these chemical parameters ranged from 394.05 to 513.50 mg/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
11
1
Order By: Relevance
“…Besides, p-coumaric acid was also detected, although it was present in trace (0.08 ± 0.01 lg/mg of extract). Our observation was found to be in accordance with R. delica, Russula lepida, Russula mustelina, Russula caerulea and Russula sardonia where cinnamic acid was also noticed as the common ingredient (Kouassi et al 2016;Alves et al 2013). On the other hand, pcoumaric acid has been identified in Agaricus arvensis, Agaricus silvicola, Lepista nuda, Boletus edulis, Tricholoma populinum, Armillaria tabescens, Psathyrella candolleana and Helvella leucopus (Barros et al 2009;Dundar et al 2015).…”
Section: Hplc Profilingsupporting
confidence: 87%
“…Besides, p-coumaric acid was also detected, although it was present in trace (0.08 ± 0.01 lg/mg of extract). Our observation was found to be in accordance with R. delica, Russula lepida, Russula mustelina, Russula caerulea and Russula sardonia where cinnamic acid was also noticed as the common ingredient (Kouassi et al 2016;Alves et al 2013). On the other hand, pcoumaric acid has been identified in Agaricus arvensis, Agaricus silvicola, Lepista nuda, Boletus edulis, Tricholoma populinum, Armillaria tabescens, Psathyrella candolleana and Helvella leucopus (Barros et al 2009;Dundar et al 2015).…”
Section: Hplc Profilingsupporting
confidence: 87%
“…Their work shows the presence of pyrogallol as the most dominant compound manifested in the extract followed by cinnamic acid. In samples studied from Côte d’Ivoire, Kouassi et al [ 21 ] evaluated the methanolic extracts, revealing that quercetin, salicylic acid, and tanninol were the main phenolic compounds identified in R. delica, while R. lepida contained gallic acid, catechin, and protocatechuic acid as the main phenolic compounds; besides these species, they also identified salicylic acid, tanninol, and catechin in R. mustelina . The different composition found can be attributed to the different solvents used for the extraction (ethanol and methanol) as well the species and environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports discussing the antioxidant activity of R. integra [ 30 ], R. lepida [ 21 , 31 ], R. nigricans [ 30 , 31 ], R. delica [ 21 , 25 , 30 , 32 ], R. vinosa [ 30 ], R. brevipes [ 31 ], R. mustelina [ 21 ], and R. cyanoxantha [ 22 ] extracts although described by different assays, namely DPPH (2,2-diphenyl-1-picryl-hydroxide) radical scavenging activity, ferric reducing power (FRAP), and the β-carotene-linoleate model system. Additionally, Khatua et al [ 33 ] showed that the rusalan (polysaccharide isolated from R. alatoreticula basidiocarps) has good antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations